STRATEGI GURU DAN PENERIMAAN MURID DALAM PELAKSANAAN PENDIDIKAN SALAT DHUHA, DZUHUR, DAN ASAR DI TADIKA DAN SEKOLAH RENDAH - Rizky Giansyah Putra; Mavianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores teacher strategies and student acceptance in the implementation of Dhuha, Dzuhur, and Asar prayer education at tadika and primary school levels in Malaysia. Early childhood prayer education requires systematic strategies aligned with children’s psychological development to transform ritual compliance into meaningful spiritual habituation. The research employs a qualitative descriptive approach, utilizing observation, in-depth interviews, and documentation to capture the dynamics of teacher-student interactions during daily prayer routines. Data were analyzed using the Miles and Huberman model, encompassing data reduction, display, and conclusion drawing, while validity was ensured through triangulation of sources, techniques, and time. Findings indicate that teachers effectively utilize modeling, habituation, demonstration, motivational reinforcement, individualized guidance, and cooperative learning to scaffold prayer implementation. Student acceptance is manifested through willingness, interest, understanding, positive attitudes, and active participation, significantly influenced by teacher consistency, school religious climate, peer influence, and family support. The study concludes that developmentally appropriate, empathetic, and consistent teacher strategies are fundamental to fostering intrinsic motivation and sustained acceptance of prayer routines among young learners. These insights provide practical implications for Islamic early childhood education policy and curriculum design, emphasizing the integration of spiritual habituation within structured yet child-centered learning environments.